Sphaeropezia leucocheila sp. nov. (Stictidaceae): a liverwort pathogen from New Zealand - Johnston, P. R.; Park, D.; Renner, M. A. M. (Phytotaxa, 2019)
Sphaeropezia leucocheila is described as a new species from New Zealand. Known from a single specimen, its fruiting bodies were consistently associated with a patch of dead and dying leaves in a liverwort colony that included several species of Lepidoziaceae. A phylogenetic analysis places this fungus in Sphaeropezia, a genus that includes several putative parasites of liverworts and mosses from the Northern Hemisphere.